Donor-Dependent Factors Influencing Contamination Rates of Conjunctival Swabs of Human Donor Eyes - Röck, Tobias (Ann Transplant, 2019)
BACKGROUND: This study investigated the effect of donor-dependent factors on contamination rates of conjunctival swabs of human donor eyes. MATERIAL/METHODS: From July 2015 to September 2017 a total of 1008 conjunctival swabs from 504 consecutive human donor eyes were analyzed. Cross-tabulation, chi-squared tests, and Fisher’s exact tests were used to evaluate the effect of donor-dependent factors on contamination rates of conjunctival swabs. RESULTS: The mean conjunctival swabs contamination rate was 28.4%. Donors with the diagnosis of carcinoma or metastases were associated with an increased conjunctival swab contamination rate [odds ratio (OR)=1.8, 95% confidence interval (CI)=1.2–2.6, p=0.007; OR=1.7, 95% CI=1.1–2.6, p=0.016; respectively]. However, the age, sex, diagnosis of diabetes mellitus, and donors who received chemotherapy did not significantly increase the conjunctival swab contamination risk. CONCLUSIONS: Donors with the diagnosis of a carcinoma or metastases seemed to be predisposed to increased conjunctival swab contamination risk.